Comparison of Milk Yield and Reproductive Performance of Sheep Breeds in the West Bank, Palestine - Jihad Abdallah; Moayed Ahmed & (My University, 2013)
The aim of this study was to compare milk production and reproductive traits of sheep breeds in the West Bank. The data included 1711 milk records on 1243 ewes and 3682 lambing records on 1837 ewes from the local Awassi breed, Assaf breed, Awassi x Assaf crosses, and two Improved Awassi strains, one of which is carrying the Booroola FecB gene. The data were collected between 2003 and 2010 from 21 farms covering five locations in southern West Bank (Dora, Hebron, Bethlehem, Jerusalem, and Ramallah) and three locations in northern West Bank (Nablus, Qalqiliya, and Jenin). The results showed significant differences (P < 0.05) in performance among and within breeds in different locations. Milk production was highest for Awassi x Assaf in Nablus and Jenin (least-squares means of 330.6 kg and 267.6 kg for total milk yield in 150 d of lactation, respectively) and Assaf in Jenin (268.1 kg), and was lowest for Awassi in Jerusalem (124.6 kg). The Improved Awassi strain carrying the FecB gene had the highest reproductive performance (mean litter size of 1.69 lambs and mean lambing interval of 304.3d), while the lowest performance was for Awassi (mean litter size of 1.12 to 1.21 lambs and mean lambing interval of 347.3 to 416.6 d). The means of litter size and lambing interval for the Improved Awassi strain not carrying the FecB gene were 1.28 lambs and 353.5d. Introgression of the FecB gene may be utilized to improve reproductive performance of sheep breeds in the West Bank, particularly Awassi.

هدفت الدراسة إلى مقارنة إنتاجية الحليب والكفاءة التناسلية لسلالات الأغنام في الضفة الغربية. واشتملت معطيات الدراسة على 1711 سجل حليب من 1243 نعجة و 3682 سجل ولادات من 1837 نعجة تعود إلى سلالة العواسي المحلي، وسلالة العساف، والسلالة الهجينة (عواسي × عساف) بالإضافة إلى صنفين من أغنام العواسي المحسن أحدهما يحمل طفرة الخصوبة FecB لأغنام البورولا. وقد تم جمع المعطيات في الفترة ما بين 2003 و2010 من 21 مزرعة توزعت على خمس مناطق في جنوب الضفة الغربية (دورا، الخليل، بيت لحم، القدس، رام الله) وثلاثة في شمال الضفة (نابلس، قلقيلية، جنين). وقد أظهرت النتائج وجود فروقات معنوية (P < 0.05) في الكفاءة الإنتاجية للحليب والكفاءة التناسلية ما بين السلالات وبين المناطق لنفس السلالة. وكانت أعلى إنتاجية حليب للأغنام الهجينية (عساف × عواسي) في نابلس وجنين (330.6 كغم و267.6 كغم في فترة حلابة 150 يوم، على التوالي) وأغنام العساف في جنين (268.1 كغم) وأقل إنتاجية كانت لأغنام العواسي في القدس (124.6 كغم). كماأظهرت النتائج أن صنف العواسي المحسن الذي يحمل جين الخصوبة كان الأفضل من حيث الكفاءة التناسلية (متوسط عدد التوائم كان 1.69 ومتوسط الفترة بين ولدتين كان 304.3 يوما) بينماكانت أقل كفاءة تناسلية لسلالة العواسي غير المحسن (متوسط عدد التوائم تراوح بين 1.12 و1.21 ومتوسط الفترة بين ولدتين تراوح بين 347.3 و416.6 يوما). أما صنف العواسي المحسن الذي لا يحمل جين الخصوبة فقد بلغ متوسط عدد التوائم 1.28 ومتوسط الفترة بين ولدتين 353.5 يوما. وتدل هذه النتائج على أنه يمكن زيادة الكفاءة التناسلية للأغنام في الضفة الغربية من خلال إدخال جين الخصوبة إليها وبخاصة في أغنام العواسي.
مقارنة إنتاجية الحليب والكفاءة التناسلية لسلالات الأغنام في الضفة الغربية - فلسطين